Macroalgal–bacterial interactions: identification and role of thallusin in morphogenesis of the seaweed Ulva (Chlorophyta). (4th February 2020) - Alsufyani, Taghreed; Califano, Gianmaria; Deicke, Michael; Grueneberg, Jan; Weiss, Anne; Engelen, Aschwin H; Kwantes, Michiel; Mohr, Jan Frieder; Ulrich, Johann F; Wichard, Thomas
Abstract: Macroalgal microbiomes have core functions related to biofilm formation, growth, and morphogenesis of seaweeds. In particular, the growth and development of the sea lettuce Ulva spp. (Chlorophyta) depend on bacteria releasing morphogenetic compounds. Under axenic conditions, the macroalga Ulva mutabilis develops a callus-like phenotype with cell wall protrusions. However, co-culturing with Roseovarius sp. (MS2) and Maribacter sp. (MS6), which produce various stimulatory chemical mediators, completely recovers morphogenesis. This ecological reconstruction forms a tripartite community which can be further studied for its role in cross-kingdom interactions. Hence, our study sought to identify algal growth- and morphogenesis-promoting factors (AGMPFs) capable of phenocopying the activity of Maribacter spp. We performed bioassay-guided solid-phase extraction in water samples collected from U. mutabilis aquaculture systems. We uncovered novel ecophysiological functions of thallusin, a sesquiterpenoid morphogen, identified for the first time in algal aquaculture. Thallusin, released by Maribacter sp., induced rhizoid and cell wall formation at a concentration of 11 pmol l −1 . We demonstrated that gametes acquired the iron complex of thallusin, thereby linking morphogenetic processes with intracellular iron homeostasis. Understanding macroalgae–bacteria interactions permits further elucidation of the evolution of multicellularity and cellular differentiation, and development of new applications in microbiome-mediated aquaculture systems. Abstract : Thallusin was isolated from sea lettuce aquacultures and assigned novel morphogenesis-inducing properties. Specifically, thallusin promoted rhizoidal zone and cell wall formation; thus, it plays crucial roles in cross-kingdom interactions.